Establishment and Implementation of Sponge City Monitoring System— A Case Study of Zhenjiang - WANG Yan; YU Meixiu; LU Zhicong (Renmin Zhujiang)
In order to effectively deal with urban water pollution and waterlogging,China proposes the concept of sponge city for stormwater management,which takes the control rate of total annual runoff,urban non-point pollution control,and urban rainstorm and waterlogging prevention as evaluation indicators to comprehensively improve the water resources,water security,water environment,and water ecological quality of cities.In the process of sponge city planning,construction,operation,and maintenance,it is necessary to establish a complete online monitoring system to assist the whole life cycle management of the sponge city construction.With Zhenjiang city listed in the first batch of pilot sponge cities in China as an example,a multi-level and organically nested sponge city monitoring system is constructed,and it mainly monitors rainfall,underlying surface,land area (sponge facilities,project sites,drainage zones),rivers and lakes,and basins.In addition,its monitoring indicator,distribution principle,monitoring frequency,as well as selection,recognition,and effective utilization of data are specified.The construction and implementation of the sponge city monitoring system are of great theoretical significance and application value for evaluating the construction and operation optimization of sponge cities,strengthening urban waterlogging prevention and control,and systematically promoting sponge cities in the whole area.